Gen Z and Tolerance: How Young People Maintain Peace in the Digital World - Nazira Maulidia Nasution; Andina Febriana Lubis; Lilis Febiola; Sugianto (Aimmah: Social Sciences Journal, 2026)
This article aims to analyze the contribution of Generation Z in maintaining and enhancing tolerance in the digital world amid the rapid development of information technology. Generation Z, as a group born and raised in a digital environment, holds an important position in shaping patterns of social interaction on the internet. This study employs a qualitative approach using a literature review method to examine Generation Z’s tolerant behavior, perspectives on tolerance from an Islamic viewpoint, various practices of tolerance, the challenges faced, and strategies for strengthening tolerance based on Islamic values. The findings show that Generation Z tends to be open to various differences, yet is also vulnerable to negative impacts from content such as hate speech and misinformation. From an Islamic perspective, tolerance is an essential element of the concept of rahmatan lil ‘alamin, which emphasizes the importance of mutual respect in diversity. The implementation of tolerance among Generation Z in the digital sphere can be seen in various forms, including the dissemination of counter-hate narratives, the application of value-based digital literacy, inter-identity collaboration, reporting intolerant content, and the use of more inclusive language. However, several challenges persist, such as the phenomenon of echo chambers, user anonymity, and low levels of digital literacy. To address these issues, strengthening efforts are needed through the integration of religious education and digital literacy, the optimization of moderate public figures’ roles, the creation of open digital communities, and the application of moderation principles in religious practices. In this way, Generation Z has great potential to act as agents of peace in creating a harmonious, inclusive, and ethical digital space.